Executive Remuneration of Listed Family Companies in Malaysia - Jong, Ling (Curtin University, 2018)
This thesis examines the executive remuneration of listed family companies in Malaysia. The research objectives are to investigate the extent of executive remuneration and the factors influencing it. By employing agency theory as the theoretical framework, this study examines the influence of family participation on board, corporate governance mechanisms and institutional ownership on executive remuneration. Random effects estimation is used for the panel analysis of five-year data from 2010 to 2014 for 279 sample companies.